An Advanced Integration Solution to Migration of Legacy System to Standard Cloud Based Global Legal Instances (International Journal of Food and Nutritional Sciences, 2022)
Data migration is the process of transferring data from one system or storage location to another. It is commonly performed when transitioning from legacy systems to new systems, upgrading software or hardware, consolidating databases, or merging organizations. Data migration to the cloud involves transferring data from on-premises systems or other cloud platforms to a cloud-based environment. Cloud migration offers numerous benefits, including scalability, cost-efficiency, flexibility, and improved accessibility. Data migration to the cloud brings several challenges that organizations should be aware of and address effectively. The proposed work gives an advanced integration solution for migrating data from legacy systems to standard cloud based global legal instances.